Estudo da sustentabilidade ambiental no Ministério Público da Paraíba sob a ótica da Agenda Ambiental da Administração Pública - A3P - Torres, Audrey Regina Leite Esperidião (2020)
Sustainability and environmental responsibility are ubiquitous terms in the debates of modern society. The concern about changes in behavior on the part of citizens and institutions, given the scarcity of natural resources, highlights the concern of public organizations with the future of the planet, in the performance of their social role. This research evaluated the main environmental problems within the scope of the Public Ministry of Paraíba (MPPB) taking as a parameter the six thematic axes of the Environmental Agenda of Public Administration (A3P). A3P is a Program of the Ministry of the Environment (MMA), of voluntary adhesion, which aims to implement socio-environmental responsibility in the administrative and operational activities of the public administration. It is characterized as an exploratory-descriptive research, with a qualitative approach, covering the administrative headquarters and other annexes of MPPB, located in João Pessoa / PB. The methodology comprises bibliographic research, document collection, applied interviews and field research. The speeches obtained with the application of the interviews were categorized in the light of the content analysis of Bardin (2007). It was found that MPPB does not institute its Environmental Policy, nor does it have a Sustainable Management Plan (PGS). The results demonstrate that the MPPB has started its path towards sustainability through isolated socioenvironmental practices, with low adherence to the A3P axes. The mainobstacles presented were: the reality of each sector, which implies the punctual adoption of sustainable practices at the manager's discretion, the absence of a socio-environmental management program or even of a commission or body responsible for this articulation; the lack of knowledge of sustainable practices already implemented in the institution; lack of training and awareness of its members regarding the environmental issue, in addition to the scarcity of financial resources. However, there are high expectations regarding the implementation of a PGS in the MPPB, mainly within the policies implemented by the institution's Strategic Planning, which has been replicating projects carried out in the A3P standard. In view of these findings and the concerns pointed out by the interviewees, we suggest: prioritizing the definition of an institutional Environmental Policy, constituting a Management Committee, for the purpose of developing and implementing a PGS that meets the environmental management program instituted for A3P adherence and the conducting an organizational diagnosis, collecting data on the socio-environmental situation MPPB, to establish, according to the institution's need, sustainability practices and rationalization of expenditures and processes in the Public Ministry of Paraíba.